HUBUNGAN ANTARA PENGETAHUAN, SIKAP DAN PENGAWASAN TERHADAP PERILAKU PEMAKAIAN APD PADA PEKERJA PABRIK PLASTIK, PRESSING DAN CASTING PT. WIJAYA KARYA INDUSTRI & KONSTRUKSI TAHUN 2022 - Dina Ghassani; Rindu Rindu; Rahmat Supriyatna (Jurnal Kesehatan Masyarakat, 2023)
Personal Protective Equipment (PPE) is the last choice of risk for the safety and health of workers from potential hazards or accidents. To improve compliance with the use of PPE the need for supervisory factors is used to control each activity to achieve the goals that have been set. This study aims to determine the relationship between knowledge, attitudes, and supervision of the behavior of using PPE in production workers in 2022. This type of research is quantitative with a cross-sectional research design. The sample is 128 production workers. The instruments in this study used measurements and questionnaires regarding knowledge, attitudes, and supervision. Data analysis was performed univariate and bivariate using the chi-square test. Based on the results of the study, it is known that there is a significant relationship between knowledge and behavior in the use of PPE, the results of the chi-square test (p-value = 0.029 <0.05) with OR = 2.308, mean that workers with poor knowledge have the opportunity to behave badly towards the use of PPE. PPE compared to workers with good knowledge, Attitude (p = 0.008) Supervision (p = 0.007) it is also known that there is a significant relationship with the behavior of using PPE for workers in Plastic, Pressing and Casting Factory PT. Wijaya Karya Industri & Konstruksi.